1993
DOI: 10.1136/gut.34.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative endoscopy of the whole small bowel in Crohn's disease.

Abstract: The aim of this study was to search for small bowel lesions by means of a perioperative endoscopy in 20 patients operated on for Crohn's disease. Seven women and 13 men (mean age 29 years) had a total retrograde exploration to the angle of Treitz during an ileocolectomy (16 of20 patients) or a colonic or ileal resection (four of20 patients). Endoscopic exploration was completed, through an enterotomy, from the surgical area to the angle of Treitz. Periendoscopic biopsy samples were taken on macroscopic lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…The significance of these lesions is uncertain; whereas some authors defend that they must be considered as disease recurrence, the lack of a careful assessment of the upper gastrointestinal tract prior to surgery makes impossible to know if they were already present before surgery. In the early nineties, Lescut et al performed a perioperative retrograde endoscopy through the enterotomy and up to the angle of Treitz in 20 CD patients undergoing ileal and/or colonic resections, and found that 65% of patients had mucosal lesions [42] . Furthermore, a prospective endoscopic evaluation of these patients did not find any relationship between endoscopic recurrence 12 wk after surgery and the presence of small bowel lesions left in place after a "curative" surgery [43] .…”
Section: Assessment Of Postoperative Recurrencementioning
confidence: 99%
“…The significance of these lesions is uncertain; whereas some authors defend that they must be considered as disease recurrence, the lack of a careful assessment of the upper gastrointestinal tract prior to surgery makes impossible to know if they were already present before surgery. In the early nineties, Lescut et al performed a perioperative retrograde endoscopy through the enterotomy and up to the angle of Treitz in 20 CD patients undergoing ileal and/or colonic resections, and found that 65% of patients had mucosal lesions [42] . Furthermore, a prospective endoscopic evaluation of these patients did not find any relationship between endoscopic recurrence 12 wk after surgery and the presence of small bowel lesions left in place after a "curative" surgery [43] .…”
Section: Assessment Of Postoperative Recurrencementioning
confidence: 99%
“…Ileocolonoscopy is useful in order to detect inflammation in colonic and distal ileal lesions, but it has a diagnostic limitation because it is impossible to reach the mid-section of the small intestine. 40-70% of CD patients have small bowel lesions [5,6,7,8]; therefore, detecting small intestinal disease is important. SBFT has been the standard radiologic approach used to assess activity of the small bowel.…”
Section: New Modalities For CDmentioning
confidence: 99%
“…As with anatomical involvement at diagnosis, changes in disease location over time should ideally be studied prospectively and systematically with a predefined imaging technique. It is now accepted that ‘unsuspected' mucosal lesions are frequently seen when the upper small bowel is explored by endoscopy instead of radiological studies [13,14]. …”
Section: Natural History Of CDmentioning
confidence: 99%